Survival rate and perioperative data of patients who have undergone hemipelvectomy: a retrospective case series. Issue 1 (December 2016) - Couto, Alfredo; Araújo, Bruno; Torres de Vasconcelos, Roberto; Renni, Marcos; Da Fonseca, Clóvis; Cavalcanti, Ismar
Abstract Background Hemipelvectomy is a major orthopedic surgical procedure indicated in specific situations. Although many studies discuss surgical techniques for hemipelvectomy, few studies have presented survival data, especially in underdeveloped countries. Additionally, there is limited information on anesthesia for orthopedic oncologic surgeries. The primary aim of this study was to determine the survival rate after hemipelvectomy, and the secondary aims were to evaluate anesthesia and perioperative care associated with hemipelvectomy and determine the influence of the surgical technique (external hemipelvectomy [amputation] or internal hemipelvectomy [limb sparing surgery]) on anesthesia and perioperative care in Brazil. Methods This retrospective case series collected data from 35 adult patients who underwent hemipelvectomy between 2000 and 2013. Survival rates after surgery were determined, and group comparisons were performed using the Kaplan–Meier method and the log-rank test. Mantel–Cox test and multiple linear regression analysis with stepwise forward selection were performed for univariate and multivariate analyses, respectively. Results Mean survival time was 32.8 ± 4.6 months and 5-year survival rate was 27 %. Of the 35 patients, 23 patients (65.7 %) underwent external hemipelvectomy and 12 patients (34.3 %) underwent internal hemipelvectomy. The survival rate was significantly higher in patients with bone tumors than in those with soft tissue sarcomas (P  = 0.024). The 5-year cumulative probability of survival was significantly lower in patients who underwent external hemipelvectomy than in those who underwent internal hemipelvectomy (P  = 0.043). In the univariate and multivariate analyses, only advanced disease stage (3 and 4) was identified as a significant independent predictor of reduced survival (P  = 0.0003). Balanced general anesthesia combined with epidural block was the most frequent anesthesia technique. Median intraoperative crystalloid volume and red blood cell transfusions were 3500 mL and 2 units, respectively. Conclusions Overall mean survival time after hemipelvectomy was 32.8 months. Advanced disease stage might be independently associated with reduced survival. Smaller amounts of fluids and transfusions were administered and time to discharge was shorter. Acute and chronic pain as well as wound complications are still important challenges in hemipelvectomy.